Le systeme européen d’acquisition d’armement. Facteur de soutien de la PESD - Cristian Iordan (Romanian Journal of European Affairs, 2010)
The European Union needs a solid and effective Security and Defence Policy. The goals of this article are to demonstrate, with recent developments in the matter, major challenges and statistic elements on defence, investment and research budgets: at first, that the process of standardisation and harmonisation at the European level are necessary steps toward the creation of a European system of defence procurement, and secondly, the link between this system and the ESDP.